Hepatic stellate cell-intrinsic role of SOCS1 in controlling hepatic fibrogenic response and the pro-inflammatory macrophage compartment during liver fibrosis - Kandhi, Rajani; Yeganeh, Mehdi; Yoshimura, Akihiko; Menendez, Alfredo; Ramanathan, Sheela; Ilangumaran, Subburaj (Frontiers in Immunology, 2023)
During liver fibrosis hepatic stellate cells (HSC) become activated, differentiate to myofibroblasts and produce extracellular fibrillar matrix. Reciprocal interaction between HSCs and macrophages orchestrates the hepatic fibrogenic response. SOCS1 can regulate signaling by certain cytokines and growth factors implicated in liver fibrosis. To investigate the role of SOCS1 in regulating HSC activation, we induced liver fibrosis using carbon tetrachloride in mice lacking SOCS1 in HSCs (Socs1 ΔHSC ) and evaluated molecular and cellular changes. Socs1 ΔHSC mice developed more severe liver fibrosis than control Socs1 fl/fl mice that was characterized by increased myofibroblast differentiation and collagen deposition. Livers of Socs1 ΔHSC mice showed significant increase in the expression of smooth muscle actin, collagens, matrix metalloproteases, cytokines, growth factors and chemokines. The livers of Socs1 ΔHSC mice displayed heightened inflammatory cell infiltration with increased proportion and numbers of Ly6C hi CCR2+ pro-inflammatory macrophages. This population contained elevated numbers of CCR2+CX3CR1+ cells, suggesting impaired transition towards restorative macrophages. Fibrosis induction following exposure to the chemical carcinogen diethyl nitrosamine resulted in more numerous and larger liver tumor nodules in Socs1 ΔHSC mice than in Socs1 fl/fl mice. Our findings indicate that SOCS1 expression in HSCs is a critical regulator of HSC activation and pro-inflammatory macrophage recruitment and differentiation during liver fibrosis and cancer development.